Expenditure on research and development activities as a determinant of the innovativeness of the European Union’s economy - Firlej, Krzysztof Adam (Nakłady na działalność badawczo-rozwojową jako determinanta innowacyjności gospodarki Unii Europejskiej, 2019)
This article aims to determine to what extent and with what time delay expenditure on research and development activity are determined by the effects of innovative activity. The accepted research hypothesis is that the positive impact of expenditure on research and development activity on its results is visible already after one or two years from when they were incurred. In order to empirically verify the proposed research hypothesis, the correlation between selected variables relating to R&D spending in 2013-2017 and selected variables determining the effects of innovative activity in 2018 in EU economies was examined. The results obtained in the study made it possible to verify the research hypothesis by confirming the important role of expenditure on research and development activity in the context of creating innovation of the economy, with particular emphasis on the financial resources of the private sector
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 7, s. 35-46
Keywords: research and development activity; innovativeness of the economy; działalność badawczo-rozwojowa; innowacyjność gospodarki